(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Craving Avenue began on July 20, 2020, and is located in Rodriguez, Rizal. Craving Avenue is a fast food restaurant that can cater to families, friends, co-workers, or a small group of companions. Craving Avenue was founded by Ethan Ezekiel Pagliwanan. Craving Avenue offers good menu options, convenient outlet design, quality, and service; it has a potential brand image in the fast food industry. In terms of quality and taste, they prefer to try something they already know customers prefer or are familiar with. Craving Avenue customers have had some issues with their product’s availability, price, quality food, and service. Based on the result, it revealed that there is no significant difference in the assessment of the employed and unemployed respondents in terms of Marketing mix, which is product, price, promotion, and place. (T-stat value -0.3238, -0.38624, -2.3590, 11.4744) with (P-value one-tailed of 0.487858, 0.359491, 0.038871, 0.000165 respectively) leads to accepting the nulled hypothesis. This marketing mix consists of controllable, tactical marketing tools that a company uses to generate the desired response in the target market. However, the challenge has motivated us to find a solution on how to provide their needs and the essentials for the customers. A page of clients who need to evaluate the marketing mix of clients and how we can continue to offer them marketing strategies on the path of desire. In terms of products, price, advertising, and location, marketing refers to activities that a business is committed to promoting the purchase or sale of products or services. This includes advertising and delivery of products to customers.